PAI (Islamic Religious Education) Teacher's Strategy in Improving Student Learning Behavior Through Learning Design - Nurul Aisyah; Ariyo Wibisono; Maria Jesus Perucha Arranz (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aims to investigate PAI teachers' strategies through learning designs at Muhammadiyah Middle Schools. This type of research is descriptive qualitative field research. Muhammadiyah Middle School in Yogyakarta is the site of this research. Three PAI teachers served as research subjects, with the research objects being PAI teacher strategies, student learning behavior, and Islamic education learning designs. Techniques for gathering data include observation, interviews, and documentation. Techniques for data analysis include data reduction, data presentation, and conclusion. According to the study's findings, there are two learning design strategies: planning and implementing learning. The planning design is adjusted to content standards and is passed down in the syllabus to the Learning Implementation Plan (RPP). At the same time, implementation is divided into three steps: opening, core activities, and closing. It begins with asking students how they are and brainstorming material. The core activities include communicating learning objectives, delivering material, and assessing students' attitudes, knowledge, and skills. The final activity, closing, is filled out by the teacher with learning reflections and conclusions.